PENGEMBANGAN MATERI AJAR TEKS CERPEN BERBANTUAN CANVA SISWA KELAS XI MAN 1 MEDAN - Thesaloni Octapia Siahaan; Dewi Pakpahan; Great Novie Parangin-angin; Nazwa Desilhan Maha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this research is to create short story text teaching materials using Canva for 11th-grade students at MAN 1 Medan. This development was undertaken because the previous teaching modules focused solely on text, lacked visual appeal, and did not integrate digital media appropriate to the needs of students born in the digital age. This research applied the ADDIE model, which includes analysis, design, and development, without involving direct implementation with students. Data was obtained through document analysis, teacher interviews, internal observations, and expert assessments. The resulting development resulted in a short story text e-module that combines visual elements, illustrations, and projectbased activities such as short story writing. Expert validation results indicated that this product is suitable for use and aligns with the Independent Curriculum, particularly in supporting creativity, digital literacy, and student learning motivation. This study concluded that Canva is effective as a tool for developing engaging, interactive short story text teaching materials that are appropriate for the characteristics of 21st-century students.